1988
DOI: 10.1038/331273a0
|View full text |Cite
|
Sign up to set email alerts
|

Loss of constitutional heterozygosity in colon carcinoma from patients with familial polyposis coli

Abstract: Recent studies have suggested a critical role of specific gene loss in several embryonic tumours and certain adult cancers. In retinoblastoma, hemizygosity or homozygosity of a recessive mutant allele results in the loss of normal gene product, and this seems to cause the manifestation of the disorder. Familial polyposis coli (FPC) is a human autosomal dominant trait characterized by numerous adenomatous polyps of the colon and rectum, and a high incidence of colon carcinoma. Karyotype analyses have failed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(39 citation statements)
references
References 32 publications
4
35
0
Order By: Relevance
“…The recently identified neurofibromatosis 2 gene (Rouleau et al 1993;Trofatter et al 1993) is localized proximal to p300 at 22q12. Chromosomal deletions, including the 22q13 region, have been detected in certain types of colon cancer (Okamoto et al 1988) and gliomas (Jenkins et al 1989). Further analysis is under way to investigate a potential involvement of p300 in these cases.…”
Section: Chromosomal Location Of the P300 Genementioning
confidence: 99%
“…The recently identified neurofibromatosis 2 gene (Rouleau et al 1993;Trofatter et al 1993) is localized proximal to p300 at 22q12. Chromosomal deletions, including the 22q13 region, have been detected in certain types of colon cancer (Okamoto et al 1988) and gliomas (Jenkins et al 1989). Further analysis is under way to investigate a potential involvement of p300 in these cases.…”
Section: Chromosomal Location Of the P300 Genementioning
confidence: 99%
“…In this study, it was found that of 31 colorectal cancers informative for chromosome 5 markers, six showed loss of heterozygosity at 5q with co-existing losses at chromosomes 17p and 18. As shown here and by others Okamoto et al, 1988) loss of heterozygosity in loci other than 18, 17p and 5q are only rarely involved in colonic cancers.…”
Section: Gastric Cancersmentioning
confidence: 79%
“…Loss of heterozygosity (LOH) on 22q has been reported in meningiomas, colorectal cancers, pheochromocytomas, and breast cancers, indicating the possible existence of tumor suppressor(s) on the chromosome arm (Dumanski et al, 1987;Okamoto et al, 1988;Tanaka et al, 1992;Shin et aI., 1993;Chert et al, 1991). Moreover, in the case of the DiGeorge syndrome (DGS), deletion of a certain region of 22qll is thought to be closely related with this disease (Driscoll et aI., 1992).…”
Section: Introductionmentioning
confidence: 99%